2016
DOI: 10.1063/1.4963070
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell bacterium identification with a SOI optical microcavity

Abstract: Photonic crystals and microcavities act as on-chip nano-optical tweezers for identification and manipulation of biological objects. Until now, optical trapping of virus and bacteria has been achieved and their presence in the vicinity of the optical resonator is deduced by the shift in the resonant wavelength. Here, we show trapping and identification of bacteria through a properly tuned silicon on insulator microcavity. Through the spatial and temporal observations of bacteria–cavity interaction, the optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…albumin (BSA) proteins [136][137][138][139][140][141][142][143], single-stranded DNA [144], optically trapped bacteria [145,146], NCI-H358 lung cancer cell line lysates [147], and human papillomavirus virus-like particles [148][149][150]. Sophisticated slotted waveguides [141,[151][152][153] as well as nanobeam cavities [140,146,150,[154][155][156][157][158][159][160] have also been implemented for analyte-specific stoichiometric studies and biomolecule micromanipulation.…”
Section: Photonic Crystals Engineered With Nano/microcavities For Intmentioning
confidence: 99%
See 3 more Smart Citations
“…albumin (BSA) proteins [136][137][138][139][140][141][142][143], single-stranded DNA [144], optically trapped bacteria [145,146], NCI-H358 lung cancer cell line lysates [147], and human papillomavirus virus-like particles [148][149][150]. Sophisticated slotted waveguides [141,[151][152][153] as well as nanobeam cavities [140,146,150,[154][155][156][157][158][159][160] have also been implemented for analyte-specific stoichiometric studies and biomolecule micromanipulation.…”
Section: Photonic Crystals Engineered With Nano/microcavities For Intmentioning
confidence: 99%
“…Sophisticated slotted waveguides [141,[151][152][153] as well as nanobeam cavities [140,146,150,[154][155][156][157][158][159][160] have also been implemented for analyte-specific stoichiometric studies and biomolecule micromanipulation. Extreme, sub-attomolar detection of a streptavidin protein was reported for nanoslot PhC nanolasers [139,[161][162][163][164][165][166][167][168], while novel PhC nanocavities combined with plasmonic nanostructures have emerged as hybrid photonic-plasmonic biosensors [169][170][171][172][173][174][175][176][177][178][179].…”
Section: Photonic Crystals Engineered With Nano/microcavities For Intmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrate here the trapping of three kinds of bacteria shown in Figure 5: Staphylococcus epidermidis (aggregated as diplococcus), Escherichia coli, and Bacillus subtilis aggregates. [8] It is found that the trapping efficiency varies depending on the bacteria shape. While B. subtilis bacteria (long rode shape) are still experiencing some non-negligible translational motion above the cavity, stable trapping is achieved in the case of S. epidermidis bacteria (spherical shape, or dimer shape) and E. coli bacteria (short rode shape).…”
Section: Bacteriamentioning
confidence: 99%